PERUBAHAN PAKAIAN PENGANTIN NAGARI TALUAK KECAMATAN BATANG KAPAS KABUPATEN PESISIR SELATAN SUMATERA BARAT - RIRI ANDRIANI, Dr. Budiwirman, M.Pd. Drs. Erwin A, M.Sn. (Universitas Negeri Padang, 2016)
This article comes from studies that have been conducted aimed to describe changes in the shape, pattern and color of the wedding dress to make it known to the local community, national and global. The method used is qualitative descriptive approach. In line with the times, then, now its creation creative motivation has shifted to the taste of the user and the community. Changes Motif on the wedding dress on the wedding dress old to the new changes, motifs used today have a variety of motives, ie motives kaluak nails, flowers rose, Bungo batabua, jasmine, while the bridal wear long had only three kinds of motives alone are florals rose, bungo batabua and kaluak nail motif. Changes in color are also more varied, had just turned red orange, yellow, brown, green, pink and blue. Conclusion The study shows there has been a change in the shape, pattern and color of the wedding dress Taluak village district subdistrict Batang Kapas South Shore. Presented to the next researcher to examine whether the change in the shape, pattern and color also changes the meaning of the clothing ?. Changes in the form trousseau now looks increasingly varied, which was once one model turns into many model.Keywords: Shape Change, Motive and Color Clothing Bride.